Scale effects of topographic ruggedness on precipitation over Qinghai‐Tibet Plateau - Ning Lu (Atmospheric Science Letters, 2019)
Abstract Due to the complex topography in mountainous areas, the pattern of precipitation is impacted by the topographic ruggedness (TR) that is characterized from Digital Elevation Model and thus scale‐dependent. Scale effects on the precipitation–TR relationship have not been well known in the Qinghai‐Tibet Plateau. Based on station measurements of precipitation in the domain, this study uses the quantile regression method to investigate the response of precipitation quantiles in summer and winter to the TR changes at different spatial scales. It is found that the scale variations impede the validity analysis of precipitation–TR relations. Neither too large (>100 km) or too small (<1 km) scales are suitable for exploring summer precipitation, and the scales are better less than 30 km for high winter precipitation. The analyses address that the precipitation–TR relations depend on appropriate spatial scales, which is important for statistical downscaling and model projection of precipitation in the Qinghai‐Tibet Plateau.